A participatory evaluation of legal support in the context of health‐focused peer advocacy with people who are homeless in London, UK. (5th December 2022) - Guise, Andy; Burrows, Martin; Marshall, Adam
Abstract: Legal problems can be cause and consequence of ill‐health and homelessness, necessitating efforts to integrate responses to these challenges. How to respond to legal issues within the context of health services for people who are homeless is though unclear. Groundswell piloted providing legal support to peer advocates (who have current or past experience of homelessness) and clients currently homeless in addition to their health‐focused work. A participatory action‐research design evaluated the emerging programme. Groundswell staff, both researchers and those involved in service delivery, co‐led the research alongside an external researcher. Qualitative methods were used to understand the experiences of legal support. We interviewed peer advocates and volunteers ( n  = 8), Groundswell clients ( n  = 3) and sector stakeholders ( n  = 3). Interviews were linked to regular reflective recorded meetings ( n  = 7) where Groundswell staff and researchers discussed the programme and the evaluation. Data were analysed thematically. The findings focus on three themes. First, peer advocates' and clients' legal needs involve an experience of being overwhelmed by system complexity. Second, the legal support to peer advocates aided in brokering and signposting to other legal support, in the context of a supportive organisational culture. Third, support to clients can be effective, although the complexity of legal need undermines potential for sustainable responses. In conclusion, legal support for peer advocates should be developed by Groundswell and considered by other similar agencies. Legal support to people who are currently street homeless requires significant resources and so health‐focused third‐sector organisations maybe unable to offer effective support. Other modes of integration should be pursued. Findings also have implications for how the third sector relates to the government agencies implicated in the legal challenges facing people who are homeless.